Sebuah Analisa Pengaruh UKM, Investasi dan Tenaga Kerja pada Pertumbuhan Pendapatan Ekonomi di Kota Batam - Ferlix Fernando Goh Goh (Politeknik Kutaraja, 2021)
This study aims to determine and analyze the impact on Small business, Workforce, and Investments on Indonesia Economic Growth, specifically in the city Batam. This type of research is a type of analysis of quantitative data that was collected from various sources through official website online. Based on our study that was conducted, At the year 2016 through 2019 Economic growth on Indonesia and Batam has experienced growth for the past years. At the year 2019 through 2020 Economic growth on Indonesia, and Batam has experienced a huge decline on its GDP. From Small business, Workforce, and Investments all have been affected massively through the year, and was caused by the impact of the recent Covid-19 Pandemic.